Noninvasive 3‐dimensional imaging of liver regeneration in a mouse model of hereditary tyrosinemia type 1 using the sodium iodide symporter gene. Issue 4 (12th March 2015) - Hickey, Raymond D.; Mao, Shennen A.; Amiot, Bruce; Suksanpaisan, Lukkana; Miller, Amber; Nace, Rebecca; Glorioso, Jaime; O'Connor, Michael K.; Peng, Kah Whye; Ikeda, Yasuhiro; Russell, Stephen J.; Nyberg, Scott L.
<x xml:space="preserve">Abstract</x> Cell transplantation is a potential treatment for the many liver disorders that are currently only curable by organ transplantation. However, one of the major limitations of hepatocyte (HC) transplantation is an inability to monitor cells longitudinally after injection. We hypothesized that the thyroidal sodium iodide symporter (NIS) gene could be used to visualize transplanted HCs in a rodent model of inherited liver disease: hereditary tyrosinemia type 1. Wild‐type C57Bl/6J mouse HCs were transduced ex vivo with a lentiviral vector containing the mouse Slc5a5 (NIS) gene controlled by the thyroxine‐binding globulin promoter. NIS‐transduced cells could robustly concentrate radiolabeled iodine in vitro, with lentiviral transduction efficiencies greater than 80% achieved in the presence of dexamethasone. Next, NIS‐transduced HCs were transplanted into congenic fumarylacetoacetate hydrolase knockout mice, and this resulted in the prevention of liver failure. NIS‐transduced HCs were readily imaged in vivo by single‐photon emission computed tomography, and this demonstrated for the first time noninvasive 3‐dimensional imaging of regenerating tissue in individual animals over time. We also tested the efficacy of primary HC spheroids engrafted in the liver. With the NIS reporter, robust spheroid engraftment and survival could be detected longitudinally after direct parenchymal injection, and this thereby demonstrated a novel strategy for HC transplantation. This work is the first to demonstrate the efficacy of NIS imaging in the field of HC transplantation. We anticipate that NIS labeling will allow noninvasive and longitudinal identification of HCs and stem cells in future studies related to liver regeneration in small and large preclinical animal models. Liver Transpl 21:442–453, 2015. © 2015 AASLD.